Stemmiulus brasiliensis n. sp., a new species of millipede from Brazilian iron ore caves (Diplopoda: Stemmiulida: Stemmiulidae) - Iniesta, Luiz Felipe Moretti; Ferreira, Rodrigo Lopes (Zootaxa, 2015)
A new species of Stemmiulus Gervais, 1844 is described from Amazonian iron ore caves located in Pará State, Brazil. The new species differs from the other Brazilian species by gonopod morphology, especially the angiocoxite and colpocoxite, and for the first pairs of legs of males. A key for the species of Stemmiulus found in Brazil is included.